To what extent do the legal restrictions on non-government organizations in Egypt undermine NGOs' ability to achieve their goals? - Hassan, Mohammed Sirajalden (AUC Knowledge Fountain, 2010)
The Egyptian civil society is the biggest civil society in the region. The current law governing non-government organizations (NGOs) in Egypt is Law 84 of 2002. This law is considered by several scholars as highly restrictive law. Non-government organizations in Egypt have faced legal restrictions on their operations and struggled for years to meet the requirements of this law. This research assesses the impact of the law on Egyptian NGO operations and their ability to pursue their missions effectively. Six areas of impact were explored based on a typology of regulatory impact adapted from the literature. Several non-government organizations were interviewed to explore and analyze the difficulties that are hindering these NGOs from achieving their goals. A written questionnaire and interviews were conducted with human rights and educational/services non-government organizations to collect detailed information about the difficulties they are facing under the current law. This exploratory research points to differences between human rights and educational/service NGOs in problems they confront in compliance with Law 84.